Shear crack width assessment in concrete structures by 2D distributed optical fiber. (15th September 2019) - Rodriguez, Gerardo; Casas, Joan R.; Villalba, Sergi
Highlights: Most of the papers that currently refer to the use of distributed optical fiber sensors (DOFS), in the Structural Health Monitoring (SHM) deal with Brillouin techniques, applied to cover long distances with poor spatial resolution. There are few works in which Rayleigh techniques are applied in the DOFS and whose objective is the location, detection and quantification of crack widths. In this paper the use of DOFS is applied for the first time in a complete study of detection, localization and quantification of cracks in concrete elements subject to shear stress, which is a more complex problem than the case of bending. Abstract: This paper outlines the second part of an experimental study to show the capabilities of distributed optical fiber sensors (DOFS) in their application to the structural health monitoring (SHM) of the shear performance of concrete structures. SHM seeks to obtain the shear crack characteristics of concrete elements: detection, localization and quantification of shear damage. The two first were discussed in the first part of the experimental study. In the present paper, the quantification is dealt with by proposing a method to obtain the mean shear crack width in concrete beams. The method is based on the experimental data obtained by a DOFS bonded to the concrete surface. First, the basis of the methodology are presented and, later on, experimentally checked by testing of three partially pre-stressed concrete (PPC) beams subjected to a shear test with increasing level of load. The DOFS were deployed in the web of the beams to conform a 2D grid mesh to measure the strain profile along two orthogonal directions. The experimental data was obtained using an OBR (Optical Backscattered Reflectometer) system with high spatial resolution and sensitivity that allow a complete mapping of the cracking pattern and to obtain the required data for the calculation of the crack width. The results show the feasibility of the proposed method in calculating the shear crack width when compared to the results from traditional instrumentation.